Evolution of water management in coastal Bangladesh: from temporary earthen embankments to depoliticized community-managed polders - Dewan, C.; Mukherji, A.; Buisson, Marie-Charlotte (Informa UK Limited, 2015)
This article examines the historical evolution of participatory water management in coastal Bangladesh. Three major shifts are identified: first, from indigenous local systems managed by landlords to centralized government agencies in the 1960s; second, from top-down engineering solutions to small-scale projects and people’s participation in the 1970s and 1980s; and third, towards depoliticized community-based water management since the 1990s. While donor requirements for community participation in water projects have resulted in the creation of ‘depoliticized’ water management organizations, there are now increasing demands for involvement of politically elected local government institutions in water management by local communities.